(untitled) (American Journal of Islam and Society, 1991)
In this book, the author offers an empirical and theoretical analysis of the relationship between the Iranian Islamic revolution and the performance of the Iranian economy. The book in divided into three main chapters plus an introduction and a conclusion. In the introduction, the author gives a profound analysis of the prerevolutionary period with a special emphasis on the Shah’s open-door economic policies which led to rapid and uneven economic growth and eventually increased Iran’s economic dependence on the capitalist world. The author also analyzes the emerging political, cultural, and social ideologies in the Iranian society which set the stage for revolution. The proclaimed aims of the revolution were listed as achieving economic development, sovereignty, and justice. These were subsequently transformed into an Islamic vision as reflected in the constitution and the first socioeconomic plan of the Islamic Republic. In the second chapter, the forces influencing the postrevolutionary economy are pointed out. The major force was the war which erupted with Iraq in the early 1980s. Apart from the destruction and loss of life, the war had an overwhelmingly negative and permanent impact on the economy ...